Felicidade interna bruta: reflexos da realidade no cerrado Goiano - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
The debate between the concepts of growth and development is not recent, the former being generally associated with the economy, while the latter is related to social factors. Publications of studies about life quality and well-being have been increased in the last years with the measuring of Gross National Happiness index - GNH. Measuring happiness allows to go beyond of social and economic data including the analyses of human feelings. This work aimed to measure the GNH index in four municipalities located in cerrado area of Goiás, Brazil: Caldas Novas, Jataí, Pirenópolis and Silvânia. Therefore the dissertation was structured in three articles. In the first article in order to compare the growth and development rates of these municipalities a bibliographic, exploratory and descriptive research was carried out by searching demographic, economic, social and environmental data of these four regions. It was observed that among 2000-2010 there was an improvement in all indices (income, education, access to public services and quality of life) in all municipalities, especially in Jataí, but it is not clear the influence of parameters of the growth in aspects of human development. The second article we carried out a scientometric analysis of scientific production about GNH index. We use the Web of Science database writing the keywords “Gross National Happiness” or “Happiness Index”. A total of 262 documents were published between 1987 and 2020, which 168 are journal articles. The most expressive number of publications comes from China, the United States and Australia, while Brazil is on the 12th position. Correlating different scientometric parameters, there is a global involvement among authors, magazines, institutions and countries in publications of studies on happiness. The third article in order to measure and analyze the relevant aspects about happiness of the people in four municipalities in State of Goiás: Caldas Novas, Jataí, Pirenópolis and Silvânia it was measured the GNH index. A bibliographic research was carried out to contextualize the theme, and a questionnaire about GNH index was applied in order to calculate this index. The higher values of the indicators of GNH index was about psychological well being and ecological diversity and resilience. It was observed that the municipalities that features best performance in social and economic data was not the ones that had the higher values for the GNH index. Jataí shows the higher values about social and economic indexes while Pirenópolis how the minors values. However Pirenópolis had the higher value for the GNH index followed by Silvânia, Jataí and Caldas Novas.
Gross national happiness: reflections of reality in the brazilian cerrado of Goiás
Keywords: Felicidade; Qualidade de vida; Bem-estar; Meio ambiente; Cerrado; Happiness; Quality of life; Well bein; Environment; Brazilian savanah; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS HUMANAS::PSICOLOGIA